Calculati:
3,1+(-4)+(-2,7)+0,9=
Răspunsuri la întrebare
Răspuns de
9
3,1+ (-4)+(-2,7)+0,9 =
= 3,1 - 4 - 2,7 + 0,9=
= 3,1 + 0,9 - 4 - 2,7 =
= 4 - 4 - 2,7 =
= 0- 2,7 =
= - 2,7
= 3,1 - 4 - 2,7 + 0,9=
= 3,1 + 0,9 - 4 - 2,7 =
= 4 - 4 - 2,7 =
= 0- 2,7 =
= - 2,7
Răspuns de
1
3,1+(-4)+(-2,7)+0,9=
3,1+(-4)=-0,9
(-0,9)+(-2,7)=-3,6
(-3,6)+0,9=-2,7
Sper ca te-am ajutat!!!
3,1+(-4)=-0,9
(-0,9)+(-2,7)=-3,6
(-3,6)+0,9=-2,7
Sper ca te-am ajutat!!!
Alte întrebări interesante
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Geografie,
8 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă